Kelimpahan Vektor Lalat Pada Peternakan Sapi Bali (Bos sondaicus) di Wilayah Perbatasan RI-RDTL, Kabupaten Malaka - Putri, Nur Layla Astika; Almet, Julianty; Wuri, Diana A; Djungu, Dewi F.L (Program Studi Kedokteran Hewan, Universitas Nusa Cendana, 2024)
The East Kobalima sub-district, which borders Timor Leste, has a cattle population of 1,673 (Central Bureau of Statistics, 2023). The existence of the Motamasin Cross Border Post makes it easier for people to trade between the two countries, especially cattle. Lack of knowledge among farmers about cattle health can lead to various cattle health problems that can harm farmers, such as uncontrolled fly infestation. This study aims to calculate the relative abundance of flies on cattle farms in the RI-RDTL border area, Malaka Regency. Fly samples were collected from 4 villages in East Kobalima sub-district, Malaka Regency. Fly samples were collected using hand collection, sweeping net and light trap methods. The collected flies were pinned and stored in a collection box for further identification of morphological characteristics and calculation of their relative abundance. The results of the fly vector abundance calculation showed that the most dominant fly species were Hippobosca sp. with up to 300 flies (71.94%), Stomoxys calcitrans with up to 111 flies (26.61%) and Musca domestica with up to 6 flies (1.43%).